Analysis and determination of diterpenoids in unprocessed and processed Euphorbia lathyris seeds by HPLCâESI-MS - Xiao-Rong Hou; Lei-Lei Wan; Zha-Jun Zhan; Cheng-Ping Li; Wei-Guang Shan (Elsevier, 2011)
Euphorbia lathyris (Caper spurge) is a toxic and potent Chinese materia medica (T/PCMM). This study sought a method for identifying five diterpenoids (Euphorbia factors L1âL3, L7a and L8) with the spectra of UV and mass, quantifying three diterpenoids L1, L2, and L8 in crude extracts of unprocessed and processed E. lathyris seeds by liquid chromatography/electrospray ionization mass spectrometry (LCâESI-MS). The analysis was achieved on an Agilent Eclipse XDB-C18 column (4.6Â mmÃ150Â mm i.d., 5Â Î¼m) with an isocratic elution with a mobile phase consisting of water and acetonitrile at a flow rate of 0.25Â mL/min at column temperature of 30Â Â°C and UV detection was set at 272Â nm. An ESI source was used with a positive ionization mode. The calibration curve was linear in the ranges of 9.9â79Â Î¼g/mL for Euphorbia factor L1, 3.8â30.5Â Î¼g/mL for Euphorbia factor L2, and 1.0â20.6Â Î¼g/mL for Euphorbia factor L8. The average recoveries (n=6) of three diterpenoids were 98.39%, 91.10% and 96.94%, respectively, with RSD of 2.5%, 2.4% and 2.1%, respectively. The contents of the three diterpenoids in processed E. lathyris seeds were 3.435, 1.367 and 0.286Â mg/g, respectively, which decreased more sharply than those in unprocessed E. lathyris seeds which were 4.915, 1.944 and 0.425Â mg/g, respectively. The method is simple, accurate, reliable and reproducible, and it can be applied to control the quality of unprocessed and processed E. lathyris seeds. Keywords: Toxic and potent Chinese materia medica (T/PCMM), High-performance liquid chromatography/electrospray ionization mass spectrometry (HPLCâESI-MS), Euphorbia lathyris, Diterpenoids